2011
DOI: 10.1016/j.stem.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Human ESC-Derived Neural Crest Model Reveals a Key Role for SOX2 in Sensory Neurogenesis

Abstract: Summary The transcription factor SOX2 is widely known to play a critical role in the central nervous system; however, its role in peripheral neurogenesis remains poorly understood. We recently developed an hESC-based model in which migratory cells undergo epithelial to mesenchymal transition (EMT) to acquire properties of neural crest (NC) cells. In this model, we found that migratory NC progenitors downregulate SOX2, but then start re-expressing SOX2 as they differentiate to form neurogenic dorsal root gangli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
103
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(127 citation statements)
references
References 60 publications
22
103
1
Order By: Relevance
“…Our previous microarray gene expression analysis of hESC-derived multipotent NPCs (11,30,31) suggested that SOX2 regulates the expression of LIN28, a well-studied repressor of let-7 family biosynthesis (13)(14)(15)(16). Immunofluorescence analysis confirmed that SOX2 and LIN28 were coexpressed in all NPCs (Fig.…”
Section: Sox2mentioning
confidence: 64%
See 3 more Smart Citations
“…Our previous microarray gene expression analysis of hESC-derived multipotent NPCs (11,30,31) suggested that SOX2 regulates the expression of LIN28, a well-studied repressor of let-7 family biosynthesis (13)(14)(15)(16). Immunofluorescence analysis confirmed that SOX2 and LIN28 were coexpressed in all NPCs (Fig.…”
Section: Sox2mentioning
confidence: 64%
“…We previously found that knocking down SOX2 precludes NPC differentiation into neurons without affecting glial fates (11). Indeed, SOX2 knockdown in NPCs cultured under conditions favoring neuronal differentiation strongly reduced the appearance of young TUJ1+ neurons ( Fig.…”
Section: Lin28 Modulates Npc Proliferation and Neuronal Commitmentmentioning
confidence: 73%
See 2 more Smart Citations
“…Rather, it is involved in a variety of fetal and adult stem cells, such as neural stem cells, retina and pituitary progenitor cells. [38][39][40][41] At the molecular level, Sox2 serves as a pioneer factor and is involved in cell fate determination through its dynamic interactions with different protein partners for transcriptional regulation of corresponding sets of target genes. [42][43][44][45] For example, in undifferentiated ES cells, Sox2 forms a heterodimer with Oct4 to activate stemness-related genes while repressing differentiationspecific genes.…”
Section: Discussionmentioning
confidence: 99%